Uji Efektivitas Nefroprotektif Ekstrak Buah Kersen (Muntingia calabura L.) Terhadap Histopatologi Dan Penanda Inflamasi Pada Tikus Putih Yang Diinduksi Gentamicin - Superman Jaya Hulu; Asyrun Alkhairi Lubis; Hariyadi Dharmawan Syahputra (Journal of Pharmaceutical and Sciences, 2026)
Background: Kidney disease remains a major global health problem, one of which is associated with the use of nephrotoxic drugs such as gentamicin. Gentamicin induces renal damage through oxidative stress and inflammatory mechanisms. Muntingia calabura L. fruit contains bioactive compounds, including flavonoids and phenolic substances, which are believed to have nephroprotective properties. Objective: This study aimed to evaluate the nephroprotective effectiveness of Muntingia calabura fruit extract on renal histopathological changes and inflammatory markers in gentamicin-induced rats. Methods: This experimental laboratory study employed a post-test only control group design. A total of 25 male white rats were divided into five groups: negative control (0.5% CMC-Na), positive control (gentamicin 80 mg/kg BW), and three treatment groups receiving gentamicin 80 mg/kg BW combined with graded doses of Muntingia calabura fruit extract (50, 100, and 200 mg/kg BW) orally for 7 days. Renal histopathology was examined using hematoxylin-eosin (HE) staining, while serum interleukin-6 (IL-6) levels were measured using enzyme-linked immunosorbent assay (ELISA). Results: Administration of Muntingia calabura fruit extract significantly reduced IL-6 levels and improved renal histopathological features compared to the positive control group (p < 0.05). The nephroprotective effect increased in a dose-dependent manner, with the highest dose (200 mg/kg BW) showing renal conditions closest to normal. Conclusion: Muntingia calabura fruit extract has potential as a natural nephroprotective agent against gentamicin-induced nephrotoxicity through inhibition of inflammatory response as indicated by decreased IL-6 levels.